Are treatments more effective than placebos? A systematic review and meta-analysis. - Howick, J; Friedemann, C; Tsakok, M; Watson, R; Tsakok, T; Thomas, J; Perera, R; Fleming, S; Heneghan, C (Public Library of Science, 2013)
Background. Placebos are widely used in clinical practice in spite of ethical restrictions. Whether such use is justified depends in part on the relative benefit of placebos compared to ‘active’ treatments. A direct test for differences between placebo and ‘active’ treatment effects has not been conducted. Objectives. We aimed to test for differences between treatment and placebo effects within similar trial populations. Data Sources. A Cochrane Review compared placebos with no treatment in three-armed trials (no treatment, placebo, and treatment). We added an analysis of treatment and placebo differences within the same trials. Synthesis Methods. For continuous outcomes we compared mean differences between placebo and no treatment with mean differences between treatment and placebo. For binary outcomes we compared the risk ratio for treatment benefit (versus placebo) with the risk ratio for placebo benefit (versus no treatment). We conducted several preplanned subgroup analyses: objective versus subjective outcomes, conditions tested in three or more trials, and trials with varying degrees of bias. Results. In trials with continuous outcomes (n = 115) we found no difference between treatment and placebo effects (MD = −0.29, 95% CI −0.62 to 0.05, P = 0.10). In trials with binary outcomes (n = 37) treatments were significantly more effective than placebos (RRR = 0.72, 95%CI = 0.61 to 0.86, P = 0.0003). Treatment and placebo effects were not different in 22 out of 28 predefined subgroup analyses. Of the six subgroups with differences treatments were more effective than placebos in five. However when all criteria for reducing bias were ruled out (continuous outcomes) placebos were more effective than treatments (MD = 1.59, 95% CI = 0.40 to 2.77, P = 0.009). Conclusions and Implications. Placebos and treatments often have similar effect sizes. Placebos with comparatively powerful effects can benefit patients either alone or as part of a therapeutic regime, and trials involving such placebos must be adequately blinded.